An Organic Semiconductor Organized into 3D DNA Arrays by "Bottom‐up" Rational Design. (3rd May 2017) - Wang, Xiao; Sha, Ruojie; Kristiansen, Martin; Hernandez, Carina; Hao, Yudong; Mao, Chengde; Canary, James W.; Seeman, Nadrian C.
Abstract: A 3D array of organic semiconductors was assembled using a DNA scaffold. An octameric aniline molecule ("octaniline") was incorporated into a DNA building block based on a dimeric tensegrity triangle. The construct self‐assembled to form a 3D crystal. Reversible redox conversion between the pernigraniline and leucoemeraldine states of the octaniline is retained in the crystal. Protonic doping gave emeraldine salt at pH 5, corresponding to the conductive form of polyaniline. Redox cycling within the crystal was visualized by color changes and Raman microscopy. The ease of conversion between the octaniline states suggests that it is a viable electronic switch within a unique 3D structure.